Insulin-like growth factor axis in pregnancy and gestational diabetes mellitus - Anderlová, K; Cinkajzlová, A; Šimják, P; Kloučková, J; Kratochvílová, H; Lacinová, Z; Kaválková, P; Krejčí, H; Mráz, M; Pařízek, A; Haluzík, M; Kršek, M (Physiological research, 2019)
The insulin-like growth factor (IGF) is involved in the regulation of growth and metabolism. The aim of this study was to determine selected parameters of IGF system at systemic and local levels [subcutaneous (SAT) and visceral adipose tissue (VAT)] to assess its possible role in gestational diabetes mellitus (GDM). 37 pregnant women (21 with GDM and 16 without GDM) and 15 age-matched non-pregnant females were included in the study. Blood samples were taken in 28-32 and 36-38 weeks of gestation and 6-12 months after delivery. SAT and VAT samples were obtained during delivery or surgery. Compared with non-pregnant women, serum IGF-1 and IGFBP-3 were increased in both groups of pregnant women. IGF-2 was elevated only in GDM women from 36 weeks of gestation culminating 6 months after delivery (p=0.003). Serum IGFBP-3 was increased and IGFBP-4 decreased in GDM women vs. pregnant women without GDM during the whole study (IGFBP-3: p?0.001 for GDM vs. non-GDM; IGFBP-4: p=0.004 for GDM vs. non-GDM). Pregnant women with GDM had decreased mRNA expression of IGF-1, IGF-1R and IGF-2R and IGFBP-4 in VAT and IGF-1R in SAT compared to pregnant women without GDM. Changes in local activity of IGF are associated with the development of GDM.
Keywords: gestační diabetes; poporodní období; Somatomedins; Subcutaneous Fat; krevní glukóza; Receptors, Somatomedin; nitrobřišní tuk; těhotenství; Postpartum Period; Time Factors; Gene Expression Regulation; podkožní tuk; Gestational Age; studie případů a kontrol; Adult; Diabetes, Gestational; regulace genové exprese; gestační stáří; Blood Glucose; ženské pohlaví; Humans; Intra-Abdominal Fat; Pregnancy; biologické markery; Insulin-Like Growth Factor Binding Proteins; časové faktory; proteiny vázající IGF; dospělí; Biomarkers; Female; somatomediny; receptory somatomedinů; lidé; Case-Control Studies